The Influence of Gender Diversity, Independent Commissioners, Audit Committees, Institutional Ownership, and Profit Management on Tax Avoidance - Rindi Laila Alawiyah; Sartika Wulandari (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
Tax avoidance is an effort to increase tax efficiency legally through takingadvantage and weaknesses in tax regulations. Management participation in the company'shighest decision making can influence tax policy and the level of compliance with tax rules.This study was conducted to determine tax avoidance practices that are influenced bygender diversity, independent commissioners, audit committees, institutional ownership,and earnings management. Through a quantitative approach, secondary data used in theform of annual reports from service sub-sector companies listed on the IDX in 2018-2022.By applying purposive sampling technique, there are 185 samples from 37 companies thatmeet the selection criteria. In this study, IBM SPSS Statistics 24 software was used as atool to analyze data using multiple linear regression methods. The results show that genderdiversity, independent commissioners, and earnings management show a negative butinsignificant direction of relationship to tax avoidance, while the audit committee andinstitutional ownership have a significant negative direction of relationship to tax avoidance.The control variables in the form of probability and company size have a significant negativerelationship direction to tax avoidance, while leverage has a significant positive relationshipdirection to tax avoidance